The Effectiveness of Recovering Losses on State Assets Policy in Dismissing Handling of Corruption - Rukmono, Bambang Sugeng; Suwadi , Pujiyono; Saiful Islam , Muhammad (Lembaga Contrarius Indonesia, 2024)
The recovery of state financial losses due to corruption in Indonesia does not reduce the criminal risk for corruptors, and the purpose of this study is to examine the effectiveness of asset forfeiture from corruption in Indonesia. This comparative normative legal research compares the recovery of state losses due to corruption in Indonesia and Saudi Arabia. This research confirms that. First, the current legal framework for collecting and seizing corruption-related assets in Indonesia must be revised to recover state financial losses. Second, the existing mechanisms need to be improved for law enforcement against corruption, particularly the recovery of state losses. When compared to Saudi Arabia, the mechanism for recovering corruption assets in Indonesia is less efficient, considering that in Saudi Arabia, corruptors may lose 70% of their wealth confiscated by the Saudi Arabian government. Third, the seizure of corrupt assets in Indonesia must use the paradigm of unexplained wealth. This approach allows for confiscating assets belonging to people whose value is grossly disproportionate to their known income and who cannot prove (using reverse proof) that they acquired the assets legally.